Trajectories of liberalisation on the European industrial relations systems: A comparative study. (17th October 2022) - Arribas Camara, Javier; Cárdenas, Luis
Abstract : The main hypothesis of this article is that labour liberalisation in the post-Fordist period has affected the three principal areas of collective bargaining coordination (coverage, dominance and control) in two different ways: by attacking the core (deregulation) and the margins (dualisation) of industrial relations. Due to differences in the institutional structures of European countries, these processes could have different effects in each country, resulting in differentiated and gradual path-dependent transformations. This hypothesis is tested by studying the institutional frameworks of industrial relations in several representative European economies: France, Germany, Greece, Italy, Poland, Spain, Sweden and the United Kingdom. Finally, we conclude that there has been a substantial modification of the role, activity and weight of collective actors in the economic system of each country as a consequence of the effect of the different forms of liberalisation on the coordination of collective bargaining. As a corollary, a shift in European Union labour policies towards a further strengthening of collective bargaining spaces is needed to give social partners greater capacity to seek coordinated solutions to contemporary economic and social problems.